Analysis of Risk Factors and Intervention Strategies for Acute Kidney Injury After Cardiac Valve Replacement [Letter] - Song Y; Yang J (Dove Medical Press, 2024)
Yanyan Song, Jian Yang Department of Cardiovascular Surgery, General Hospital of Ningxia Medical University, Yinchuan, 750004, People’s Republic of ChinaCorrespondence: Yanyan Song, Department of Cardiovascular Surgery, General Hospital of Ningxia Medical University, No. 804 Shengli South Street, Xingqing District, Yinchuan, 750004, People’s Republic of China, Email nxfysyy@163.com